MODE COUPLING IN A VISCOELASTIC SELF-GRAVITATING SPHERICAL EARTH INDUCED BY AXISYMMETRIC LOADS AND LATERAL VISCOSITY VARIATIONS - Wu P. (My University, 2002)
The importance of mode coupling in a viscoelastic self-gravitating spherical earth with lateral variations in linear or nonlinear rheology is investigated with a finite-element model coupled to Poisson's equation. Both the lateral viscosity variations and the harmonic load are axisymmetric. The effects of self-gravitation, viscosity contrast and the location of the abrupt lateral change in viscosity in a linear mantle are studied and are found to be significant in determining the strength of mode coupling. It is demonstrated that a larger number of harmonics than generally assumed is required to give accurate description of the induced deformation. Mode coupling is also found to be important in a nonlinear mantle especially when the harmonic degree l is large.
Keywords: GLACIAL REBOUND; MANTLE DYNAMICS; RHEOLOGY; VISCOELASTICITY; LATERAL HETEROGENEITY